Right-to-Work Laws and the Extent of Unionization - Farber, Henry S. (Journal of Labor Economics, 1984)
It is a well-known fact that the extent of unionization is less in states with right-to-work (RTW) laws. A framework is developed for determining whether RTW laws actually cause a decrease in the extent of unionization or whether they simply mirror preexisting tastes of workers against unions. A set of empirical tests is proposed that can distinguish between these explanations based on differences between RTW and non-RTW states in the demand for union representation, the supply of union jobs relative to that demand, and the observed union/nonunion wage differential. These tests are implemented using disaggregated data from the Quality of Employment Survey and the Current Population Survey, and a pattern is found that is consistent with the hypothesis that RTW laws simply mirror preexisting preferences against union representation.